Understanding Student Perceptions and Preferences for Teachers’ Feedback in Inclusive Classrooms - Sharma, B. Umeshkumar; Rositta, M. Ugin (JOURNAL OF INDIAN EDUCATION, 2023)
The aim of this research is to explore students’ perceptions and preferences for teacher feedback practices in inclusive classrooms. Participants of this study are students of Grades VI–VIII from Kendriya Vidyalaya schools in Chennai, Tamil Nadu, India. To address the research questions and hypotheses in this survey study, three different sets of data analysis were carried out using SPSS 21. Results of this study generally showed that perception and preference of female students and non-CwSN students had positively significant relationships. Also found that teachers praised female students more than male students, and the majority of students, including CwSN, prefer to receive feedback by emphasising mistakes and providing detailed, step-by-step instructions for correcting them. The study’s findings have major implications for teachers working in inclusive classrooms, including the necessity to provide a detailed process, considering the time for feedback, balance among students, and mode of feedback.